Patterned alignment of nematic liquid crystals generated by inkjet printing of gold nanoparticles and emissive carbon dots on both flexible polymer and rigid glass substrates. Issue 6 (2nd May 2016) - Sharma, Anshul; Hofmann, Daniel; Hegmann, Torsten
ABSTRACT: Patterned homeotropic alignment using nanoparticles (NPs) was achieved using inkjet printing. Two types of gold NPs, one smaller and one larger in core diameter (2 and 5 nm) capped with a monolayer of dodecanethiol, and emissive carbon dots with a core diameter of 2.5 nm featuring a mixed ligand shell of carboxylic acid groups and aliphatic hydrocarbon chains were tested on both rigid glass and flexible polycarbonate substrates. To define the director across the entire cell and not just in the NP-printed areas, alignment 'underlayers' were tested, and 30° obliquely evaporated SiO x as alignment 'underlayer' generally provided the best results with the highest quality of the homeotropic alignment as well as the best contrast at the boundary between printed and non-printed (i.e. homeotropic and planar) domains of the fabricated cells. We also report that the chemical nature of the nematic liquid crystal (LC) used, the number of layers printed and the composition of the nano-ink need to be adjusted to obtain pattern alignment devices that positively benefit from both the properties of the LC and the nanomaterial printed. Graphical Abstract: